Silicon disease resistance, and yield of rice genotypes under upland cultural conditions - Winslow, M. (Wiley, 1992)
Silicon deficiency limits rice (Oryza sativa L.) yield on highly weathered upland soils in West Africa and can increase susceptibility to some diseases. A study at Onne, Nigeria, examined responses of different genotypes to increasing Si supply under upland cultural conditions. Without applied Si, average shoot Si concentration was one-fifth of the minimum recommended value for rice, confirming deficiency. Application of 18.7 g Si m−2 as sodium metasilicate doubled plant Si concentration and increased grain yield by 48%, and significantly reduced the severity of husk discoloration, neck blast, sheath blight, and leaf scald diseases. When grown in flooded paddies on the same soil at Onne, and on a more fertile Alfisol at Ibadan, mean leaf Si concentrations were two to three times greater than in Si-treated upland plots, and diseases were negligible. Under upland cultivation, African japonica upland rice genotypes had 50 to 100% higher Si concentration in mature flag leaves, and were more resistant to husk discoloration and neck blast, than Asian indica upland genotypes. The japonicas were equally susceptible to leaf scald, however, and more susceptible to sheath blight than the indicas. It is concluded that increasing the supply of Si to the crop through flooding is the most effective method of ameliorating Si deficiency. Where this is not practical, genes for higher Si content can probably reduce losses to some diseases, but other genetic factors seem also to have major effects.